Evaluation of STD/AIDS prevention programs: a review of approaches and methodologies Avaliação de programas de prevenção de DST/AIDS: revendo abordagens e metodologias - Marly Marques da Cruz; Elizabeth Moreira dos Santos; Simone Monteiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The article presents a review of approaches and methodologies in the evaluation of STD/AIDS prevention programs, searching for theoretical and methodological support for the institutionalization of evaluation and decision-making. The review included the MEDLINE, SciELO, and ISI Web of Science databases and other sources like textbooks and congress abstracts from 1990 to 2005, with the key words: "evaluation", "programs", "prevention", "STD/AIDS", and similar terms. The papers showed a predominance of quantitative outcome or impact evaluative studies with an experimental or quasi-experimental design. The main use of evaluation is accountability, although knowledge output and program improvement were also identified in the studies. Only a few evaluative studies contemplate process evaluation and its relationship to the contexts. The review aimed to contribute to the debate on STD/AIDS, which requires more effective, consistent, and sustainable decisions in the field of prevention. O artigo apresenta uma revisão de abordagens e metodologias sobre avaliação de programas de prevenção de DST/AIDS, buscando um aporte teórico-metodológico que subsidie a institucionalização da avaliação e a tomada de decisão. A revisão foi realizada nas bases de dados do MEDLINE, SciELO, ISI Web of Science e outras fontes, tais como livros, textos e resumos apresentados em congressos, no período de 1990 a 2005, das palavras-chave: "avaliação", "programas", "prevenção", "DST/AIDS" e termos similares. Nos artigos levantados há uma predominância de estudos avaliativos quantitativos de resultado ou de impacto, do tipo experimental ou quase-experimental. O principal uso da avaliação é o da prestação de contas, embora a produção do conhecimento e a melhoria do programa possam ser identificados nos estudos examinados. Poucos são os estudos avaliativos que contemplam a avaliação de processo e discutem a sua relação com os contextos. Pretendeu-se, com essa revisão, contribuir na tematização e aprofundamento de um debate relevante no cenário das políticas de enfrentamento das DST/AIDS, que requer respostas mais efetivas, consistentes e sustentáveis no campo da prevenção.